AUDIT MANAJEMEN - Yusup, Maulana (Majalah Bisnis & IPTEK, 2021)
In organizing various business activities, one of the challenges facing the company is how to improve the effectiveness, efficiency and economizing company. This challenge is always there because the management company needs resources to achieve the objectives of the company, but management had to face a situation of scarcity of resources. Therefore, the company should make proper planning in allocating its resources in support of operations to be done to achieve the goals set. Keywords: audit management; human Resources